Soft magnetic metal particles, powder magnetic core, and magnetic component

By forming a multi-layer insulating film composed of Fe, Ti and Si on the soft magnetic metal particles, the problem of insufficient initial magnetic flux rate of the powder core in the prior art is solved, and a soft magnetic material with high initial magnetic flux rate is realized, which is suitable for high-performance inductors and transformers.

JP2025059733APending Publication Date: 2025-04-10TDK CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023170014
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-29
Publication Date
2025-04-10

AI Technical Summary

Technical Problem

The prior art is difficult to provide the soft magnetic metal particles and powder cores required for high power inductors and transformers with high initial permeability μi.

Method used

Soft magnetic metal particles having a specific hierarchy structure are used, and the surface is covered with a multi-layer insulating film composed of Fe, Ti and Si. The insulating film includes a first layer (at least Fe), a second layer (at least Ti) and a third layer (at least Si) and is formed by sol-gel technology.

Benefits of technology

The initial flux rate of the powder core is significantly improved, suitable for high-performance inductors and transformers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025059733000001_ABST
    Figure 2025059733000001_ABST
Patent Text Reader

Abstract

To provide soft magnetic metal particles that can provide a powder magnetic core having a high initial permeability μi.SOLUTION: A soft magnetic metal particle includes a core particle and an insulating film formed on the surface of the core particle. The insulating film has a first layer, a second layer, and a third layer. The first layer is in contact with the surface of the core particle, and the second layer is in contact with the first layer and the third layer. The first layer contains at least Fe, the second layer contains at least Ti, and the third layer contains at least Si.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to soft magnetic metal particles, powder magnetic cores, and magnetic components. [Background technology]

[0002] Patent Document 1 describes that the aspect ratio of the flat powder is controlled, and that the insulating coating that covers the flat powder is made of a polymer containing titanium alkoxides.

[0003] Patent Document 2 describes a magnetic material containing soft magnetic alloy particles coated with multiple types of oxide films. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2015 / 033825 [Patent Document 2] JP 2018-11043 A Summary of the Invention [Problem to be solved by the invention]

[0005] One embodiment of the present disclosure provides soft magnetic metal particles that can provide a powder magnetic core with high initial permeability μi. [Means for solving the problem]

[0006] The soft magnetic metal particles according to an embodiment of the present disclosure include A core particle and an insulating film formed on a surface of the core particle, the insulating film has a first layer, a second layer, and a third layer; the first layer is in contact with a surface of the core particle, the second layer is in contact with the first layer and the third layer, The first layer contains at least Fe, the second layer contains at least Ti, and the third layer contains at least Si.

[0007] A powder magnetic core according to an embodiment of the present disclosure contains the above-described soft magnetic metal particles.

[0008] A magnetic component according to an embodiment of the present disclosure includes the above-described soft magnetic metal particles. [Brief description of the drawings]

[0009] [Figure 1] FIG. 2 is a schematic cross-sectional view of a powder magnetic core according to an embodiment of the present disclosure. [Diagram 2] TEM images and various mapping images of the cross section of a soft magnetic metal particle. [Diagram 3] This is an image of the insulating film periphery in FIG. 2 enlarged in the film thickness direction. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, an embodiment of the present disclosure will be described with reference to the drawings. The embodiment of the present disclosure described below is an example for explaining the present disclosure. Various components according to the embodiment of the present disclosure, such as numerical values, shapes, materials, and manufacturing processes, can be modified or changed within a range that does not cause technical problems.

[0011] Furthermore, the shapes and the like shown in the drawings of this disclosure do not necessarily correspond to the actual shapes and the like, since the shapes and the like may be modified for the purpose of explanation.

[0012] As shown in FIG. 1, a powder magnetic core 1 according to an embodiment of the present disclosure includes metal magnetic particles (core particles) 11 and a grain boundary phase 12. It further includes an insulating film 13 formed on a surface 11a of the core particle 11. The insulating film 13 has a first layer 13a, a second layer 13b, and a third layer 13c. The second layer 13b is in contact with the first layer 13a and the third layer 13c. The first layer 13a contains at least Fe. The second layer 13b contains at least Ti. The third layer 13c contains at least Si. The insulating film 13 may also have a layer outside the third layer 13c that is different from the third layer 13c.

[0013] A soft magnetic metal particle according to an embodiment of the present disclosure includes a core particle 11 and an insulating film 13 formed on a surface 11a of the core particle 11. The insulating film 13 further includes an insulating film 13 formed on the surface 11a of the core particle 11. The insulating film 13 has a first layer 13a, a second layer 13b, and a third layer 13c. The second layer 13b contacts the first layer 13a and the third layer 13c. The first layer 13a contains at least Fe. The second layer 13b contains at least Ti. The third layer 13c contains at least Si. The insulating film 13 may also have a layer different from the third layer 13c on the outside of the third layer 13c.

[0014] A dust core having soft magnetic metal particles having the above configuration tends to have a high initial permeability μi.

[0015] The thickness of the insulating film 13 may be 5 nm or more and 500 nm or less, or may be 10 nm or more and 200 nm or less.

[0016] The thickness of the second layer 13b may be 1.0% or more and 75.0% or less, or may be 2.0% or more and 50.0% or less, relative to the thickness of the insulating film 13. When the thickness of the second layer 13b is 2.0% or more and 50.0% or less relative to the thickness of the insulating film 13, the initial permeability μi tends to be high.

[0017] There is no particular limit to the thickness of the first layer 13a relative to the thickness of the insulating film 13. For example, it may be 10.0% or more and 35.0% or less. There is no particular limit to the thickness of the third layer 13c relative to the thickness of the insulating film 13. For example, it may be 10.0% or more and 70.0% or less.

[0018] The thickness of each of the first layer 13a, the second layer 13b, and the third layer 13c is 0.7 nm or more. In other words, a layer having a thickness of less than 0.7 nm is not considered to be the first layer 13a, the second layer 13b, or the third layer 13c.

[0019] There is no particular limitation on the Fe content in the first layer 13a. For example, the Fe content may be in the range of 50.0 at % to 95.0 at % relative to the total content of Fe, Si, and Ti.

[0020] There is no particular limitation on the Ti content in the second layer 13b. For example, the Ti content may be 1.0 at % or more and 10.0 at % or less with respect to the total content of Fe, Si, and Ti.

[0021] The second layer 13b may further contain Si. The Ti content ratio to the total content of Si and Ti in the second layer 13b (hereinafter, simply referred to as Ti / (Si+Ti)) may be 7.5 at% or more and 20.0 at% or less. When Ti / (Si+Ti) is 7.5 at% or more and 20.0 at% or less, the initial permeability μi tends to be high.

[0022] The content of Si in the third layer 13c is not particularly limited, and may be, for example, 50.0 at % or more and 90.0 at % or less with respect to the total content of Fe, Si, and Ti.

[0023] The third layer 13c may further contain Fe. The Ti / (Si+Ti) in the second layer 12b may be 7.5 at% or more and 20.0 at% or less, and the Fe content ratio to the total content of Fe and Si in the third layer 13c (hereinafter, simply referred to as Fe / (Si+Fe)) may be 10.0 at% or more and 50.0 at% or less. In such a case, the initial permeability μi is particularly likely to be high.

[0024] There is no particular limitation on how Fe is contained in the first layer 13a. For example, as described below, when the core particle 11 contains Fe, an oxide of Fe may be contained. When the core particle 11 contains Fe and other elements, an oxide of Fe and oxides of other elements may be contained, or a composite oxide of Fe and other elements may be contained. In addition, the first layer 13a may contain a compound other than an oxide containing Fe.

[0025] There is no particular limit to how Ti is contained in the second layer 13b. For example, simple Ti may be scattered in the second layer 13b. Also, the second layer 13b may contain a compound containing Ti. There is no particular limit to the type of compound containing Ti. For example, an organometallic compound containing Ti such as titanium alkoxide or titanate (metal complex with Ti as the central metal) may be mentioned. Also, the compound containing Ti may be a simple oxide of Ti or a composite oxide of Ti and another element. The second layer 13b may contain a composite oxide of Si and Ti.

[0026] The first layer 13a, the second layer 13b, and / or the third layer 13c may contain an oxide of Si. There is no particular limit to the type of the oxide of Si. For example, it may be a Si-O-based oxide (silicon oxide). There is no particular limit to the type of the Si-O-based oxide. For example, it may be an oxide of Si such as SiO2, or a composite oxide containing Si and other elements.

[0027] The components of the core particle 11 are not particularly limited as long as they contain a material exhibiting soft magnetism, but the core particle 11 may contain Fe. When the core particle 11 contains Fe as a main component, the saturation magnetization tends to be high. When the core particle 11 contains Fe and Si as main components, the initial permeability μi tends to be high. When the core particle 11 contains Fe and Ni as main components, the initial permeability μi tends to be high. When the core particle 11 contains Fe and Co as main components, the initial permeability μi tends to be high.

[0028] In addition, "contains as a main component" means that the content ratio of each of the elements contained as the main components is 1% by weight or more, the total content ratio of the elements contained as the main components is 40% by weight or more, and the content ratio of each of the elements other than the elements contained as the main components is lower than the content ratio of the element with the lowest content ratio among the elements contained as the main components.

[0029] When the core particle 11 contains Fe as a main component, the content of Fe is 40% by weight or more, and the content of each element other than Fe is lower than the content of Fe. There is no particular limitation on the type of component other than the main component in the core particle 11. Examples of the type of component other than the main component (Fe) include Ni, Co, Si, Zr, V, etc.

[0030] When the core particle 11 contains Fe and Si as the main components, the Fe content is 1% by weight or more, the Si content is 1% by weight or more, the total Fe and Si content is 40% by weight or more, and the content of each element other than Fe and Si is lower than the content of the element having the lower content ratio among Fe and Si. There is no particular restriction on the type of components other than the main components in the core particle 11. Examples of the types of components other than the main components (Fe and Si) include Ni, Co, Zr, V, etc.

[0031] When core particle 11 contains Fe or Fe and Si as a main component, there is no particular limitation on the content ratio of Fe and Si in core particle 11. The weight ratio of Si / Fe may be 0 / 100 to 20 / 80. When the weight ratio of Si / Fe is 0 / 100 to 10 / 90, the saturation magnetization tends to be high.

[0032] When the core particle 11 contains Fe and Ni as the main components, the Fe content is 1% by weight or more, the Ni content is 1% by weight or more, the total content of Fe and Ni is 40% by weight or more, and the content of each element other than Fe and Ni is lower than the content of the element having the lower content of Fe and Ni. There is no particular restriction on the type of components other than the main components in the core particle 11. Examples of the types of components other than the main components (Fe and Ni) include Co, Si, Zr, V, etc.

[0033] When core particle 11 contains Fe or Fe and Ni as a main component, there is no particular limitation on the content ratio of Fe and Ni in core particle 11. The weight ratio may be Ni / Fe=0 / 100 to 75 / 25.

[0034] When core particle 11 contains Fe and Co as main components, the Fe content is 1 wt% or more, the Co content is 1 wt% or more, the total Fe and Co content is 40 wt% or more, and the content of each element other than Fe and Co is lower than the content of the element having the lower content among Fe and Co. There is no particular restriction on the type of components other than the main components in core particle 11. Examples of the types of components other than the main components (Fe and Co) include Ni, Si, Zr, V, etc.

[0035] When core particle 11 contains Fe or Fe and Co as a main component, there is no particular limitation on the content ratio of Fe and Co in core particle 11. The weight ratio may be Co / Fe=0 / 100 to 50 / 50.

[0036] The insulating film 13 does not have to cover the entire surface 11a of the core particle 11, but only needs to cover 90% or more of the entire surface 11a of the core particle 11.

[0037] The insulating film 13 is formed directly on the surface of the core particle 11. That is, the surface 11a of the core particle 11 and the insulating film 13 are in contact with each other.

[0038] In addition to Fe and Ti, the insulating film 13 may contain metal elements other than Fe and Ti. Examples include Ba, Ca, Mg, Al, Zr, Ni, Mn, and Zn, whose oxides are insulating. Among them, Ca, Mg, Zr, Ni, Mn, and Zn are relatively easy to introduce into the insulating film. There is no particular limit to the content of the metal elements other than Fe and Ti. For example, the content ratio of the metal elements to the total content of Fe and Ti may be (1) mol% or less.

[0039] There is no particular limitation on the method for determining whether the insulating film 13 has the first layer 13a, the second layer 13b, and the third layer 13c. The determination can be made using SEM-EDS, STEM-EDS, TEM-EDS, or the like.

[0040] For example, a TEM image of a cross section of a soft magnetic metal particle and mapping images of Fe, Ti, Si and O created using TEM-EDS are shown in Fig. 2. The bright field area at the bottom of the TEM image in Fig. 2 corresponds to the core particle 11 in Fig. 1, and the dark field area below the core particle 11 corresponds to the insulating film 13 in Fig. 1.

[0041] FIG. 3 shows an enlarged view of the periphery of the insulating film 13 in FIG. 2 in the film thickness direction. From the mapping images in FIGS. 2 and 3, it can be seen that Fe is contained in large amounts in the first layer 13a and the second layer 13b of the insulating film 13. It can be seen that Ti is contained in large amounts in the second layer 13b of the insulating film 13. It can be seen that Si is contained in the largest amount in the third layer 13c of the insulating film 13, and is next in amount to the first layer 13a. It can be seen that O is contained in large amounts in all of the first layer 13a to the third layer 13c. That is, it can be seen by TEM-EDS that the insulating layer 13 has the first layer 13a containing at least Fe, the second layer 13b containing at least Ti, and the third layer 13c containing at least Si.

[0042] An example of a method for measuring the thickness of the insulating film 13 and the thickness of each layer will be described below, however, the method for measuring the thickness of the insulating film 13 and the thickness of each layer is not limited to the following method.

[0043] The thickness of the insulating film 13 can be measured from a TEM image. There is no particular limitation on the magnification of the TEM image, and it may be any magnification that allows confirmation of the thickness of the insulating film 13. For example, it may be 100,000 times or more and 500,000 times or less.

[0044] The position of the second layer 13b in the insulating film 13 can be confirmed by performing a line analysis of Ti using TEM-EDS. Specifically, first, a line analysis is performed in the film thickness direction of the insulating film 13 using TEM-EDS. Next, the peak of the signal intensity obtained is determined excluding the baseline. Then, the signal intensity at the peak is set to 100%, and the portion where the signal intensity is 20% or more is set to the second layer 13b. Then, the portion of the insulating film 13 closer to the core particle 11 than the second layer 13b is set to the first layer 13a, and the portion of the insulating film 13 farther from the core particle 11 than the second layer 13b is set to the third layer 13c.

[0045] The thickness of each layer can be confirmed from the position of each layer identified by the above method.

[0046] There is no particular limitation on the method for measuring the composition of each layer. For example, the composition of each layer can be measured by setting a sufficient number of measurement points in each layer, calculating the composition of each measurement point using EDS, and averaging the results.

[0047] A grain boundary phase 12 is contained between the soft magnetic metal particles contained in the powder magnetic core 1. There is no particular limit to the type of compound contained in the grain boundary phase 12. For example, the compound may be a silicone resin, an epoxy resin, an imide resin, and / or a Si-O-based oxide. The grain boundary phase 12 may also include voids. Examples of the silicone resin that may be contained in the grain boundary phase 12 include methyl-based silicone resins. Examples of the epoxy resin include cresol novolac. Examples of the imide resin include bismaleimide.

[0048] In addition, a part or the whole of the silicone resin contained in the grain boundary phase 12 may be modified into a Si-O-based oxide such as SiO2 by the heat treatment described later.

[0049] There are no particular limitations on the content of core particles 11 and the content of the compound contained in grain boundary phase 12. The content of core particles 11 in the entire powder core 1 may be 90% by weight to 99.9% by weight. The content of the compound contained in grain boundary phase 12 in the entire powder core 1 may be 0.1% by weight to 10% by weight.

[0050] There are no particular limitations on the method for observing the cross section of the powder core 1. For example, the powder core 1 may be observed at an appropriate magnification using an SEM, STEM, or TEM. Furthermore, the composition at each point of the powder core 1 can be measured by performing EDS analysis.

[0051] A method for producing the powder magnetic core 1 according to this embodiment will be described below, but the method for producing the powder magnetic core 1 is not limited to the method described below.

[0052] First, the core particles 11 are prepared. There is no particular limit to the method for preparing the core particles 11, and examples thereof include gas atomization and water atomization. There is no particular limit to the particle size and circularity of the core particles 11. When the median particle size (D50) is 1 μm to 100 μm, the initial permeability μi tends to be high. The circularity of the core particles 11 may be, for example, 0.5 to 1, 0.7 to 1, or 0.8 to 1.

[0053] Next, the insulating film 13 is formed on the surface 11 a of the core particle 11 .

[0054] First, a first layer 13a is formed on the surface 11a of the core particle 11. There is no particular limit to the method for forming the first layer 13a. When the core particle 11 contains Fe, the first layer 13a may be formed by oxidizing the surface of the core particle 11. There is no particular limit to the method for oxidizing the surface of the core particle 11. For example, heat treatment may be performed in an atmosphere containing oxygen. The thickness of the first layer 13a can be controlled by appropriately adjusting the oxygen concentration in the atmosphere, the heat treatment temperature, and the heat treatment time.

[0055] Alternatively, the first layer 13a containing Fe may be formed by coating the core particle 11 with a coating solution containing Fe.

[0056] Next, the second layer 13b is formed on the surface of the first layer 13a. There is no particular limit to the method of forming the second layer 13b. For example, a method of applying a coating solution containing alkoxysilane and Ti to the core particle 11 is exemplified. If Si is not contained in the second layer 13b, the alkoxysilane may not be contained in the coating solution. There is no particular limit to the method of applying the coating solution to the core particle 11, and for example, a method by spray diffusion is exemplified. There is no particular limit to the state in which Ti is contained in the coating solution. For example, Ti may be contained as titanium alkoxide, or Ti may be contained as titanate. When Ti is contained as titanate or titanium alkoxide and the compact is subjected to heat treatment as described later, the titanate or titanium alkoxide is decomposed by the heat treatment. The case of adding titanium alkoxide to the coating solution will be described below.

[0057] There are no particular limitations on the concentration of alkoxysilane, the concentration of titanium alkoxide, or the type of solvent in the coating solution. The concentration of alkoxysilane and the concentration of titanium alkoxide may be determined based on the desired value of Ti / (Si+Ti), the desired thickness of the insulating film 13, and the like.

[0058] Examples of alkoxysilanes include monoalkoxysilanes, dialkoxysilanes, trialkoxysilanes, and tetraalkoxysilanes. Examples of monoalkoxysilanes include trimethylmethoxysilane, trimethylethoxysilane, and trimethyl(phenoxy)silane. Examples of dialkoxysilanes include dimethyldimethoxysilane, dimethyldiethoxysilane, diisopropyldimethoxysilane, diisobutyldimethoxysilane, t-butylmethyldimethoxysilane, and t-butylmethyldiethoxysilane. Examples of trialkoxysilanes include ethyltrimethoxysilane, ethyltriethoxysilane, vinyltrimethoxysilane, methyltrimethoxysilane, n-propyltriethoxysilane, decyltrimethoxysilane, decyltriethoxysilane, and phenyltrimethoxysilane. Examples of tetraalkoxysilanes include tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, and tetraisopropoxysilane. As the alkoxysilane, one type of alkoxysilane may be used, or two or more types of alkoxysilanes may be used in combination.

[0059] Examples of titanium alkoxides include titanium tetramethoxide, titanium tetraethoxide, titanium tetra-n-propoxide, titanium tetraisopropoxide, and titanium tetra-n-butoxide. As the titanium alkoxide, one type of titanium alkoxide may be used, or two or more types of titanium alkoxides may be used in combination. From the viewpoint of availability, the titanium alkoxide may be titanium tetraethoxide or titanium tetra-n-butoxide.

[0060] Examples of the solvent include water, ethanol, and isopropyl alcohol.

[0061] Furthermore, during spraying and diffusing, the ratio of alkoxysilane to the total amount of core particles 11 may be 0.1% by weight to 5% by weight. Furthermore, the more alkoxysilane there is, the thicker the film of second layer 13b tends to be.

[0062] The conditions for spraying and diffusing are not particularly limited, but by performing spraying and diffusing while carrying out a heat treatment at 50° C. to 90° C., the sol-gel reaction for forming the second layer 13b is likely to be promoted.

[0063] After the coating solution is sprayed and diffused, the core particles 11 are dried to remove the solvent, and then heated at 200° C. to 400° C. for 1 to 10 hours to promote the sol-gel reaction and form the second layer 13b. The higher the heating temperature and the longer the heating time, the higher the density of the second layer 13b tends to be.

[0064] Regarding the case where titanate is added to the coating solution, it is the same as the case where titanium alkoxide is added to the coating solution, except that the above-mentioned titanium alkoxide is replaced with titanate. As the titanate, titanium acetylacetonate, titanium tetraacetylacetonate, titanium ethylacetoacetate, titanium octylene glycolate, titanium lactate, titanium triethanolamine, titanium diethanolamine, etc. can be exemplified. As the titanate, one kind of titanate can be used, or two or more kinds of titanates can be used in combination.

[0065] Next, a third layer 13c is formed on the surface of the second layer 13b. There is no particular limit to the method of forming the third layer 13c. For example, a method of applying a coating solution containing an alkoxysilane to the core particle 11 is exemplified. There is no particular limit to the method of applying the coating solution to the core particle 11, and for example, a method by spray diffusion is exemplified. There is no particular limit to the type of alkoxysilane, and the above-mentioned types of alkoxysilane may be used. There is no particular limit to the type of solvent, and the above-mentioned types of solvent may be used.

[0066] Furthermore, during spraying and diffusing, the ratio of alkoxysilane to the total amount of core particles 11 may be 0.1% by weight to 5% by weight. As the amount of alkoxysilane increases, the film thickness of third layer 13c tends to increase.

[0067] The conditions for spraying and diffusing are not particularly limited, but by performing spraying and diffusing while carrying out a heat treatment at 50° C. to 90° C., the sol-gel reaction for forming the third layer 13c is likely to be promoted.

[0068] After the coating solution is sprayed and diffused, the core particles 11 are dried to remove the solvent, and then heated at 200° C. to 400° C. for 1 to 10 hours to promote the sol-gel reaction and form the third layer 13c. The higher the heating temperature and the longer the heating time, the higher the density of the third layer 13c tends to be.

[0069] There is no particular limitation on the method for making the third layer 13c contain Fe. For example, a compound containing Fe may be further added to the coating solution. Examples of the compound containing Fe include iron acetate, iron chloride, and iron sulfate.

[0070] There are no particular limitations on the concentration of the alkoxysilane, the concentration of the compound containing Fe, or the type of solvent in the coating solution. The concentration of the alkoxysilane and the concentration of the compound containing Fe may be determined based on the desired value of Fe / (Si+Fe), the desired film thickness of the third layer 13c, and the like.

[0071] Next, in the case where the grain boundary phase 12 in the green compact before the heat treatment described later contains a resin, a resin solution is prepared. In addition to the above-mentioned silicone resin, epoxy resin and / or imide resin, a curing agent may be added to the resin solution. There is no particular limit to the type of curing agent, and an example of the curing agent is epichlorohydrin. There is also no particular limit to the solvent of the resin solution, and a volatile solvent may be used. For example, acetone, ethanol, etc. can be used. In addition, the total concentration of the resin and the curing agent may be 10 to 80% by weight when the entire resin solution is 100% by weight.

[0072] Next, the core particles 11 with the insulating film 13 formed thereon are mixed with a resin solution. That is, the soft magnetic metal particles are mixed with the resin solution. Then, the solvent of the resin solution is volatilized to obtain granules. The obtained granules may be filled into a mold as is, or may be sized before being filled into a mold. There are no particular limitations on the sizing method when sizing, and for example, a mesh with an opening of 45 to 500 μm may be used.

[0073] Next, the obtained granules are filled into a mold of a predetermined shape and pressed to obtain a green compact. There is no particular limit to the pressure applied during pressing (compacting pressure), and it can be, for example, 500 to 1500 MPa. The higher the compacting pressure, the higher the initial permeability μi of the finally obtained powder core 1.

[0074] When comparing a case in which the insulating film 13 has all of the first layer 13a to the third layer 13c with a case in which the insulating film 13 does not have one or more layers, even if the molding pressure is the same, the initial permeability μi of the powder core 1 is higher when the insulating film 13 has all of the first layer 13a to the third layer 13c.

[0075] The produced powder compact may be used as a powder core. The produced powder compact may be heat-treated, and a sintered body produced by the heat treatment may be used as a powder core. There are no particular limitations on the conditions for the heat treatment. When a silicone resin is used as the resin, the heat treatment may be performed under conditions that allow the silicone resin to be sintered. For example, the heat treatment may be performed at 400°C to 1000°C for 0.1 to 10 hours. There are no particular limitations on the atmosphere during the heat treatment, and the heat treatment may be performed in air or in a nitrogen atmosphere.

[0076] When the compact contains titanate or titanium alkoxide, the titanate or titanium alkoxide may be partially or entirely decomposed by the above heat treatment. In particular, titanate can be entirely decomposed by heat treatment at 700° C. or higher and 1000° C. or lower. In other words, titanate can be prevented from being contained in the sintered compact by heat treatment at 700° C. or higher and 1000° C. or lower.

[0077] Although the powder magnetic core and the manufacturing method thereof according to the present embodiment have been described above, the powder magnetic core and the manufacturing method thereof according to the present disclosure are not limited to the above embodiment.

[0078] The applications of the powder magnetic core of the present disclosure are not particularly limited. Examples of the applications include magnetic parts such as inductors, reactors, choke coils, and transformers. The magnetic parts of the present disclosure include the above-mentioned powder magnetic core. EXAMPLES

[0079] The present disclosure will be described below based on more detailed examples, but the present disclosure is not limited to these examples.

[0080] As the metal magnetic particles (core particles), Fe-Si alloy particles (alloy particles containing Fe and Si as main components) with a weight ratio of Si / Fe=4.5 / 95.5 and a total amount of Fe and Si of 99% by weight or more were produced by gas atomization. The median particle size (D50) of the Fe-Si alloy particles was 30 μm, and the circularity was about 0.90.

[0081] First, a first layer was formed on the surface of the metal magnetic particles. The first layer was formed by oxidizing the surface of the metal magnetic particles. Specifically, the metal magnetic particles were heat-treated at 800°C in a nitrogen atmosphere with an adjusted oxygen concentration to form the first layer. The oxygen concentration and heat treatment time were set so that the film thickness of the first layer would be the values ​​shown in Tables 1 to 4. The oxygen concentration was 0.1 to 1.0%, and the heat treatment time was 1 to 10 hours.

[0082] Next, coating solutions for forming the second and third layers were prepared.

[0083] The coating solution for forming the second layer (hereinafter, sometimes referred to as the coating solution for the second layer) was prepared by mixing 15 parts by weight of ethanol, trimethoxysilane, titanium tetra-n-butoxide, and 2.0 parts by weight of pure water, with the total amount of the metal magnetic particles being 100 parts by weight. The ratio of trimethoxysilane to titanium tetra-n-butoxide was set so that the Ti / (Si+Ti) in the second layer of the insulating film finally obtained would have the values ​​shown in Tables 1 to 4. The total amount of trimethoxysilane and titanium tetra-n-butoxide was set so that the film thickness of the second layer finally obtained would have the values ​​shown in Tables 1 to 4.

[0084] The coating solution for forming the third layer (hereinafter, sometimes referred to as the coating solution for the third layer) was prepared by mixing 15 parts by weight of ethanol, trimethoxysilane, and an aqueous solution of iron acetate, with the total amount of the metal magnetic particles being 100 parts by weight. The ratio of trimethoxysilane to the aqueous solution of iron acetate and the concentration of the aqueous solution of iron acetate were set so that the Fe / (Si+Fe) ratio in the third layer of the insulating film finally obtained would be the value shown in Tables 1 to 4. In the samples shown in Tables 1 to 3, pure water was appropriately mixed in place of the aqueous solution of iron acetate. The total amount of trimethoxysilane and the aqueous solution of iron acetate or pure water was set so that the film thickness of the third layer finally obtained would be the value shown in Tables 1 to 4.

[0085] In each of the Examples except Comparative Example 1, a second layer was formed on the surface of the first layer. The metal magnetic particles on which the first layer was formed were mixed with a coating solution for the second layer, and heat-treated while being sprayed and diffused. The heat treatment temperature was 80°C, and the heat treatment time was 1 hour. Furthermore, by drying after the heat treatment, metal magnetic particles on which a second layer was formed on the surface of the first layer were obtained. Note that in Comparative Example 1 in Table 1, a second layer was not formed.

[0086] Next, in each of the Examples except Comparative Example 1, a third layer was formed on the surface of the second layer. The metal magnetic particles on which the first and second layers had been formed were mixed with a coating solution for the third layer, and heat-treated while being sprayed and diffused. The heat treatment temperature was 80°C, and the heat treatment time was 1 hour. Furthermore, by drying after the heat treatment, metal magnetic particles on which a third layer had been formed on the surface of the second layer were obtained.

[0087] In Comparative Example 1, a third layer was formed on the surface of the first layer. The metal magnetic particles on which the first layer was formed were mixed with a coating solution for the third layer, and heat-treated while being sprayed and diffused. The heat treatment temperature was 80°C, and the heat treatment time was 1 hour. Furthermore, by drying after the heat treatment, metal magnetic particles on which a third layer was formed on the surface of the first layer were obtained.

[0088] The obtained metal magnetic particles were passed through a 140 mesh sieve and then heat-treated at 300° C. for 5 hours.

[0089] Next, a resin solution was prepared by mixing silicone resin and acetone. Shin-Etsu Silicone KR-242A (manufactured by Shin-Etsu Chemical Co., Ltd.) was used as the silicone resin. The silicone resin and acetone were mixed so that the weight ratio was 34:66.

[0090] The total amount of the above metal magnetic particles was 100 parts by weight, and 6 parts by weight of the above resin solution was added and mixed. The mixture was then dried to volatilize the acetone and obtain granules. The granules were then passed through a 42 mesh sieve to size them. The obtained granules were dried on a hot plate at 50°C for 0.5 hours to produce granulated powder.

[0091] 0.1 parts by weight of zinc stearate was added to 100 parts by weight of the granulated powder, and the mixture was molded to obtain a toroidal core. The amount of the granulated powder packed was 5 g. The molding pressure was adjusted so that the density of the final toroidal powder core was 6.4 g / cm. 3 The shape of the mold was a toroidal shape with an outer diameter of Φ17.5 mm, an inner diameter of Φ10.0 mm, and a thickness of 4.8 mm.

[0092] The obtained toroidal core was subjected to a heat treatment at 700° C. for 1 hour to obtain a toroidal powder magnetic core. The final powder magnetic core was set to 100% by weight, with the metal magnetic particles constituting approximately 98% by weight.

[0093] TEM-EDS observation confirmed that in each example, the insulating film included the first to third layers, while in Comparative Example 1, the insulating film included only the first and third layers.

[0094] In each example, the thickness of the insulating film was measured from a TEM image, and the position of the second layer was identified by line analysis of TEM-EDS observation. The thickness of the second layer was identified from the position of the second layer. The part of the insulating film that is inside the second layer, i.e., the part close to the core particle, was regarded as the first layer, and the thickness of the first layer was identified. The part of the insulating film that is outside the second layer, i.e., the part far from the core particle, was regarded as the third layer, and the thickness of the third layer was identified.

[0095] The thickness of the insulating film was measured by measuring the total thickness of the layers that were darker than the metal magnetic particles in the TEM image. The results are shown in Tables 1 to 4.

[0096] Next, Ti / (Si+Ti) in the second layer was quantified by EDS. Ten measurement points were set in the second layer, and Ti / (Si+Ti) at each measurement point was averaged. The results are shown in Tables 1 to 4.

[0097] Next, Fe / (Si+Fe) in the third layer was quantified by EDS. Ten measurement points were set in the third layer, and the Fe / (Si+Fe) at each measurement point was averaged. The results are shown in Tables 1 to 4.

[0098] In Comparative Example 1, the first layer and the third layer were distinguished by TEM-EDS line analysis. Composition analysis was performed for C, O, Si, Fe, and Ti, and the portion with an Fe concentration of 50 at% or more was determined to be the first layer, and the portion with an Si concentration of 20 at% or more was determined to be the third layer. Then, based on the results of the distinction, the film thickness of each layer was measured. The results are shown in Table 1.

[0099] The initial permeability μi of the toroidal powder magnetic core was measured by winding 50 turns of wire around the toroidal powder magnetic core and using an LCR meter (LCR428A from HP). An initial permeability μi of 40.0 or more and less than 45.0 was rated as good, 45.0 or more and less than 50.0 was rated as even better, 50.0 or more and less than 55.0 was rated as even better, and 55.0 or more was rated as best.

[0100] The density of the toroidal powder magnetic core was calculated from the dimensions and weight of the obtained powder magnetic core. 3 It was confirmed that the extent

[0101] [Table 1]

[0102] [Table 2]

[0103] [Table 3]

[0104] [Table 4]

[0105] As can be seen from Table 1, when the thickness of the insulating film and the density of the toroidal powder magnetic core were roughly the same, Examples 1a, 1 to 10, which included all of the first to third layers, had better initial permeabilities μi than Comparative Example 1, in which the insulating film did not include the second layer. Examples 1 to 9, in which the thickness of the second layer was 2.0% or more and 50.0% or less relative to the thickness of the insulating film, had better initial permeabilities μi than Examples 1a and 10, in which the thickness of the second layer was less than 2.0% or more than 50.0% relative to the thickness of the insulating film.

[0106] From Table 2, it can be seen that the initial permeability μi was improved even when the thickness of the insulating film was changed from that of Example 4 in Table 1.

[0107] Examples 17 to 24 in Table 3 are examples in which the Ti / (Si+Ti) in the second layer was changed from Example 4 in Table 1. Examples 18 to 23 in which the Ti / (Si+Ti) in the second layer was 7.5 at% or more and 20.0 at% or less had better initial permeability μi than Examples 4, 17, and 24 in which the Ti / (Si+Ti) in the second layer was less than 7.5 at% or more than 20.0 at%.

[0108] Examples 25a and 25 to 30 in Table 4 are examples in which the Fe / (Si+Fe) in the third layer was changed from Example 21 in Table 3. Sample numbers 25 to 29, in which the Fe / (Si+Fe) in the third layer was 10.0 at% or more and 50.0 at% or less, had better initial permeability μi than Examples 21, 25a, and 30, in which the Fe / (Si+Fe) in the third layer was less than 10.0 at% or more than 50.0 at%.

[0109] [Note] The technology according to the present disclosure includes the following configuration examples, but is not limited to these.

[0110] The soft magnetic metal particles according to one configuration example of the present disclosure include A core particle and an insulating film formed on a surface of the core particle, the insulating film has a first layer, a second layer, and a third layer; the first layer is in contact with a surface of the core particle, the second layer is in contact with the first layer and the third layer, The first layer contains at least Fe, the second layer contains at least Ti, and the third layer contains at least Si.

[0111] In the soft magnetic metal particles, a thickness of the second layer relative to a thickness of the insulating film may be 2.0% or more and 50.0% or less.

[0112] In any of the above soft magnetic metal particles, the second layer may further contain Si, and the Ti content in the second layer may be 7.5 at % or more and 20.0 at % or less with respect to the total content of Si and Ti.

[0113] In any of the soft magnetic metal particles described above, the third layer may further contain Fe, and the Fe content relative to the total content of Fe and Si in the third layer may be 10.0 at % or more and 50.0 at % or less.

[0114] In any of the above soft magnetic metal particles, the core particle may contain Fe.

[0115] In any of the above soft magnetic metal particles, the insulating film may have a thickness of 10 nm or more and 200 nm or less.

[0116] A powder magnetic core according to one configuration example of the present disclosure includes any of the soft magnetic metal particles described above.

[0117] A magnetic component according to one configuration example of the present disclosure includes any of the soft magnetic metal particles described above. [Explanation of symbols]

[0118] 1...Powder magnetic core 11 Metallic magnetic particles (core particles) 11a Surface of Metallic Magnetic Particles 12...grain boundary phase 13. Insulating film 13a...1st layer 13b...2nd layer 13c...Third layer

Claims

1. A core particle and an insulating film formed on a surface of the core particle, the insulating film has a first layer, a second layer, and a third layer; the first layer is in contact with a surface of the core particle, the second layer is in contact with the first layer and the third layer, Soft magnetic metal particles, wherein the first layer contains at least Fe, the second layer contains at least Ti, and the third layer contains at least Si.

2. 2. The soft magnetic metal particle according to claim 1, wherein the thickness of the second layer is 2.0% or more and 50.0% or less of the thickness of the insulating film.

3. 3. The soft magnetic metal particle according to claim 2, wherein the second layer further contains Si, and the content of Ti relative to the total content of Si and Ti in the second layer is 7.5 at % or more and 20.0 at % or less.

4. 4. The soft magnetic metal particle according to claim 3, wherein the third layer further contains Fe, and the content of Fe in the third layer with respect to the total content of Fe and Si is 10.0 at % or more and 50.0 at % or less.

5. The soft magnetic metal particle according to any one of claims 1 to 4, wherein the core particle contains Fe.

6. 5. The soft magnetic metal particle according to claim 1, wherein the insulating film has a thickness of 10 nm or more and 200 nm or less.

7. A powder magnetic core comprising the soft magnetic metal particles according to any one of claims 1 to 4.

8. A magnetic part comprising the soft magnetic metal particles according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Magnetic material and electronic component

    JP2018011043A

  • Insulator-coated powder for magnetic member

    WO2015033825A1